2019
DOI: 10.1038/s41598-019-54407-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of TP53 lesions for p53 system functionality and drug resistance in multiple myeloma using an isogenic cell line model

Abstract: Recent advances in molecular diagnostics have shown that lesions affecting both copies of the gene for tumor suppressor protein 53 (TP53) count among the most powerful predictors for high-risk disease in multiple myeloma (MM). However, the functional relevance and potential therapeutic implications of single hits to TP53 remain less well understood. Here, we have for the first time approximated the different constellations of mono- and bi-allelic TP53 lesions observed in MM patients within the frame of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Following that, the related analysis indicated that lncRNA NEAT1 was negatively associated with CR, ORR, PFS, and OS in MM patients, suggesting the potential of lncRNA NEAT1 as a prognostic biomarker in MM. The possible reason might be that according to the prior studies, lncRNA NEAT1 is involved in p53‐dependent DNA damage response network, which has connection with increased chemotherapy resistance in MM patients 21,27 . Furthermore, considering our data that patients with high lncRNA NEAT1 expression presented poor systematic disease condition, MM patients with high lncRNA NEAT1 had poor treatment response and unfavorable survival.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Following that, the related analysis indicated that lncRNA NEAT1 was negatively associated with CR, ORR, PFS, and OS in MM patients, suggesting the potential of lncRNA NEAT1 as a prognostic biomarker in MM. The possible reason might be that according to the prior studies, lncRNA NEAT1 is involved in p53‐dependent DNA damage response network, which has connection with increased chemotherapy resistance in MM patients 21,27 . Furthermore, considering our data that patients with high lncRNA NEAT1 expression presented poor systematic disease condition, MM patients with high lncRNA NEAT1 had poor treatment response and unfavorable survival.…”
Section: Discussionmentioning
confidence: 71%
“…The possible reason might be that according to the prior studies, lncRNA NEAT1 is involved in p53-dependent DNA damage response network, which has connection with increased chemotherapy resistance in MM patients. 21,27 Furthermore, considering our data that patients with high lncRNA NEAT1 expression presented poor systematic disease condition, MM patients with high lncRNA NEAT1 had poor treatment response and unfavorable survival.…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, in a cohort of patients with relapsed MM, TP53 abnormalities were identified in 45% of the patients, and the double hit event del(17p)/TP53mut or del(17p)/TP53del was present in 15% of the cases [112,113]. Second hits (del17p+ TP53 point mutation) abolish the remaining p53 activity and increase resistance to melphalan [110]. Deletions of chromosome 17p13 in TP53 result in shorter median event-free survival (EFS) (14.6 months) and median OS (22.4 months) [114].…”
Section: Drug Resistance To Melphalanmentioning
confidence: 92%
“…DNA damage in peripheral blood mononuclear cells is a predictor of clinical outcome in patients treated with high-dose melphalan and ASCT [109]. Moreover, genetic lesions affecting both alleles of the tumor suppressor gene TP53 are major indicators of unfavorable prognosis in newly diagnosed MM [110]. Only 3.7% of patients are diagnosed with biallelic changes in the TP53 gene in the form of a loss or mutation (called double-hit myeloma) [111].…”
Section: Drug Resistance To Melphalanmentioning
confidence: 99%
See 1 more Smart Citation